Flavivirus-Mosquito Interactions - Huang, Yan-Jang S.; Higgs, Stephen; Horne, Kate McElroy; Vanlandingham, Dana L. (My University, 2014)
The Flavivirus genus is in the family Flaviviridae and is comprised of more than 70 viruses. These viruses have a broad geographic range, circulating on every continent except Antarctica. Mosquito-borne flaviviruses, such as yellow fever virus, dengue virus serotypes 1–4, Japanese encephalitis virus, and West Nile virus are responsible for significant human morbidity and mortality in affected regions. This review focuses on what is known about flavivirus-mosquito interactions and presents key data collected from the field and laboratory-based molecular and ultrastructural evaluations.
Citation: Huang, Y.-J.S.; Higgs, S.; Horne, K.M.; Vanlandingham, D.L. Flavivirus-Mosquito Interactions. Viruses 2014, 6, 4703-4730.
Keywords: Aedes Mosquito; Culex Mosquito; Flavivirus; Hemorrhagic Fever